The Republican South : democratization and partisan change - Lublin, David, 1968- (Princeton University Press, 2004)
"This comprehensive and in-depth look at southern politics in the United States challenges conventional notions about the rise of the Republican Party in the South. David Lublin argues that the evolution of southern politics must be seen as part of a process of democratization of the region's politics. The Voting Rights Act of 1965 provided a sharp jolt forward in this process by greatly expanding the southern electorate." "Nevertheless, Democrats prevented Republicans from capitalizing rapidly on these changes. The overwhelming dominance of the region's politics by Democrats and their frequent adoption of conservative positions made it difficult for the GOP to attract either candidates or voters in many contests. However, electoral rules and issues gradually propelled the Democrats to the Left and more conservative white voters and politicians into the arms of Republican Party."--Jacket.